Home Automation Using Hand Gesture Recognition - Anisha M. R., Ashwin S. Nair, B. Aravind Reddy, Chinnannagari Tharun, Neethu K. N. (International Journal of Modern Agriculture, 2021)
Automation is the new trend, and it is the future of mankind. The quantity of tasks that must be done in a short period of time is so huge that human intervention is not possible. Automation is an integral part when it comes to fields like Data Science and Data Analytics. Home Automation is a major subdivision under automation and makes our lives way easier. We propose a system that automates low power consuming appliances at home with the help of simple hand gestures. The proposed system will of great help to the old aged members who find it extremely difficult to operate such appliances.